Adopting Project Based Learning in Translation Class to Facilitate Translator Emergent Competences - Sugeng Hariyanto; Achmad Suyono; Fitrotul Maulidiyah; Kun Mustain (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: The teaching of language-related skills in universities and colleges needs to equip students with relevant skills suitable for work after graduation. One way of building students’ skills to meet the related industry’s demands is by adopting project based learning (PBL) in teaching. There have been several studies on the topic of PBL in translation courses, but none of them have provided a step-by-step classroom procedure. Methodology: The study was a case study to describe the model of project-based learning adopted in the English Department of one Polytechnic in Java island, Indonesia. The object of the study was the Localization and Transcreation class. The data sources included the teacher and 24 sixth-semester students taking the class. Questionnaires and interview were used for the data collection. The questionnaires were used to know the students’ perceived competences. The interview was used to get more information on how the PBL was conducted and students’ further opinion about it. Before a class was started, the students were asked to fill in the provided questionnaire on the status of their competence at the time. Then, the PBL was employed to teach the class. After the PBL was done, the students were asked to fill in the same questionnaire to report their competences at the time. The researcher analyzed the results. Finally, an interview was conducted with the teacher and three students who answered the questionnaire most comprehensively. Findings: The findings of this study show that PBL could be employed to teach translation in vocational higher education and the students saw PBL positively. Based on the students’ opinion, this research found that PBL in the translation class helped students develop their translation skills, teamwork skills, workplace skills, communication skills, and self-confidence. Conclusion: In conclusion, PBL employed in the translation class has shown its effectiveness in improving students’ translation and other competences. Originality: The Ministry of National Education of the Republic of Indonesia has promoted project-based learning. To date, no clear model has been developed for the teaching of translation in Indonesian universities. This article describes project-based learning developed and practiced in a Polytechnic and how students react and the improvement of their competences or skills.